ANALISA BIAYA MEKANISASI PRODUKSI KOMPOS SISTEM WINDROW - Wahyono, Sri; L. Sahwan, Firman (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The large scale composting activity needs mechanical equipments foroperational efficiency like The Cakung Slaughterhouse has been done.Installation of mechanical equipments and buildings make it costly compare tomanual composting activities. The cost of mechanical composting need to becounted such as investment, operation and maintenance cost in order to getthe specific cost of compost production. This can be used for pricing compostproduct. According to the analysis, the best pricing for compost product is morethan Rp. 807/kg, for example Rp. 1000/kg compost. It means that CakungSlaughterhouse need increase gradually the existing compost price from Rp.500/kg to Rp. 1000/kg compost. It need for guarantying for sustainable compostproduction.Key Words: Slaughterhouse, mechanical compost, specific cost